Perceptions of ecosystem services and disservices associated with open water swimming. (March 2022) - Wood, Louisa E.; Vimercati, Giovanni; Ferrini, Silvia; Shackleton, Ross T.
Abstract: Open water swimming is becoming an increasingly popular recreational activity. Understanding the human well-being benefits that open water swimmers derive from interaction with outdoor spaces is fundamental to environmental decision making, yet little is currently known about the benefits, threats and needs of open water swimmers in relation to the environments they swim in. In this study we provide a balanced assessment of the perceived cultural ecosystem services (CES) and ecosystem disservices (EDS) experienced by open water swimmers in the UK. Factor analysis based on an online questionnaire with 505 respondents revealed three distinct clusters of CES benefits that contribute to human well-being ('spiritual value and interaction with nature', 'mental and physical health', and 'social bonds'). Swimming frequency, site type, gender and whether respondents were members of environmental groups affected response patterns towards CES benefits. There were five distinct clusters of EDS ('natural hazards', 'security and safety (health)', 'security and safety (weather)', 'recreation' and 'material (biotic and abiotic)'. Key EDS ranked as an issue (by more than 50% of respondents) related to water quality, currents, rubbish and litter in water bodies and boat traffic. Swimming duration, age and swimming frequency in particular affected response patterns surrounding EDS, and to a small extent the site type. The results can be used to support the effective implementation of national and international policy, which aims to improve human well-being through encouraging use of outdoor spaces, whilst promoting the conservation and sustainable use of freshwater and marine ecosystems. Management implications: The results of this study support effective ecosystem management of aquatic environments used by recreational open water swimmers through: - Facilitating the inclusion of cultural ecosystem services/ ecosystem disservices experienced by open water swimmers in management planning - Identifying the main human well-being benefits experienced by open water swimmers when interacting with waterbodies and demonstrating that these vary depending on the demographics of the recreational user, and characteristics of the recreational activity - Understanding the main ecosystem disservices experienced by open water swimmers and identifying management actions to address these - Providing a framework that can be used for similar assessments